PERAN RUANG RELAKSASI PADA PERANCANGAN BERKONSEP KREATIF UNTUK PENINGKATAN KREATIVITAS KARYAWAN KANTOR 24SLIDES INDONESIA - Aurellia Cintana Satya Nagara; Hana Kireina Widiyanti; Mellani Vionita; Rizquita Tsania; Ira Audia Agustina (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2021)
In the creative industries offices, all of the employees are required to work professionally with creative and innovative ideas. According to the professional work that already mentioned before, the positive feedback and customer’s satisfaction will be easily achieved. The perfect results behind are cannot be detached from the office's atmosphere and team collaboration within the office itself. A study research conveys if a company treats their workers as valuable assets, it will brings reciprocity from their workers. That is a perfect and convenient output. It is relatable with one of the 24Slides office's vision which prioritizes the happiness and joy of their employees in order to produce optimal results. Cooperative companies will make way to improve the performance and motivation of workers by facilitating and designing offices that are exhilarating and professional. If a creative industry office requires new creativity and innovation ideas, then a relaxation facility with some communicative games is recommended to stimulate the brain. Providing these facilities will restore workers' enthusiasm before taking a break or starting an activity. Lounge facilities or lounge rooms are also not provided that simple way. With an attractive interior design, it could be the other proponent as well as supporting housing from the office. Thus, the authors make a study research related to the design of a relaxation room that suitable for the 24Slides office. The purpose of this research is to figuring out the creativity and productivity enhancement of workers with the existence of a relaxation room, knowing the responses of workers, and designing concepts. Design Thinking is used as a method of this research, consisting of emphatisize, define, ideate, prototype and test. Data collection was carried out by conducting interviews with 5 respondents and a field survey at the 24Slides office. The data analysis carried out in the form of assessing existing analyzes, field surveys and interviews that had been obtained. The results of this study will be used as a reference to carry out the design of the relaxation room (funspace) at the 24Slides Indonesia office.